On micro-damage in hot metal working. Part 1: Experimental investigation - Liu, Y.; Foster, A. D.; Lin, J.; Farrugia, D. C.J.; Dean, T.A. (Engineering Transactions, 2006)
An experimental programme was defined and performed to investigate the characteristics of micro-damage for a plain CMn and a free machining steel under hot forming conditions. To investigate damage locations - at grain boundaries and around second phase inclusions - a series of constant strain rate tests were carried out on the free machining steel, which contained manganese sulphide inclusions. Specimens from both materials were strained to failure under tension using a Gleeble material simulator at a constant temperature of 1273 K, with strain rates $\dot{ε}$ = 0.01–10 s$^{-1}$. The damage characteristics of the two different steel microstructures was analysed through microstructural examinations of the tested specimens. Particular attention is focussed on damage locations and features. To investigate the recovery of materials between the intervals of hot deformation, a series of two-step tensile tests were carried out at 1273 K and 10 s$^{-1}$. The two-step specimens were initially deformed to a strain varying from 0.3–0.7, held for varying recovery periods of 0.3–10 s, then stretched to failure. Flow stress features and strains to failure during the second stage of deformation were analysed with respect to different recovery periods and strain levels at the first stage of deformation. The damage features discovered from the experimentation and microstructural examination provide theoretical evidence to form unified viscoplastic damage constitutive equations for hot forming of free machining steels, which are described in the companion paper.